Lubrication state identification of the line contact tribo-pair under a pure rolling condition with ultrasonic method. (May 2022) - Duan, Zhihe; Wu, Tonghai
A line contact tribo-pair is a key mechanism unit in rolling bearings, which is often characterized by ultra-high contact pressure and ultra-thin oil film. Elastohydrodynamic lubrication is often adopted to characterize the lubrication state of such a tribo-pair. As a primary parameter for elastohydrodynamic lubrication, the oil film thickness is often evaluated with simplified theoretical models or complicated measurements. So far, a comprehensive verification of the lubrication states in a real line-contact tribo-pair, however, is rarely reported. Focusing on the roller/ring tribo-pair of a wet-lubricated rolling bearing under pure rolling conditions, this study investigates the lubrication states by integrating multiple theories. Five regions including isoviscous hydrodynamic, piezoviscous hydrodynamic, elastohydrodynamic lubrication, mixture lubrication, and boundary lubrication regions can be identified using the framework. Then, validation experiments are carried out on a line contact tribo-pair test rig under the same operating conditions applied in the theoretical analysis. The oil film thickness is measured by the ultrasonic method. The analysis results demonstrate that only two regions, the elastohydrodynamic lubrication and mixture lubrication regions, can be identified using the experimental data. The identified elastohydrodynamic lubrication and mixture lubrication regions are consistent with theoretical analysis; and the Blok equation and elastohydrodynamic lubrication theory are suggested to calculate the oil film thickness in the elastohydrodynamic lubrication and mixture lubrication regions, respectively. Moreover, the oil film thickness calculated by the Dowson equation is larger than that based on the elastohydrodynamic lubrication theory due to a different viscous pressure equation.